The Multifaceted Role of Heme in Cancer - Fiorito, Veronica; Chiabrando, Deborah; Petrillo, Sara; Bertino, Francesca; Tolosano, Emanuela (Frontiers in Oncology, 2020)
Heme, an iron-containing porphyrin, is of vital importance for cells due to its involvement in several biological processes, including oxygen transport, energy production and drug metabolism. Besides these vital functions, heme also bears toxic properties and, therefore, the amount of heme inside the cells must be tightly regulated. Similarly, heme intake from dietary sources is strictly controlled to meet body requirements. The multifaceted nature of heme renders it a best candidate molecule exploited/controlled by tumor cells in order to modulate their energetic metabolism, to interact with the microenvironment and to sustain proliferation and survival. The present review summarizes the literature on heme and cancer, emphasising the importance to consider heme as a prominent player in different aspects of tumor onset and progression.